Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kinerja Staf Tata Usaha Pada Kantor UPTD TK, SD, dan Pendidikan Non Formal Kecamatan Sumedang Selatan Kabupaten Sumedang - Maulana Rizky Fajar; Deti Apriyanti (CV. Ulil Albab Corp, 2022)
Human resources are an important part in an institution so as to improve the quality of human resources, it is necessary to know what are the factors in improving the quality of human resources, one of which is competence. This study aims to determine the effect of competence on the performance of administrative staff of UPTD Kindergarten, Elementary, and Non-Formal Education, South Sumedang District, Sumedang Regency. The type of research conducted is descriptive and quantitative research. The population of this study was the administrative staff of UPTD TK, SD, and Non-Formal Education, South Sumedang District, Sumedang Regency, which amounted to 9 people and all of them were be sampling in this study and were asking to answer questionnaires. Based on the analysis, it can be concluding that the resulting of regression equation shows that competence has a positive and insignificant effect on the performance of administrative staff. The correlation coefficient value shows a value of 0.423, which means that the relationship between competence and the performance of administrative staff is moderate. The coefficient of determination has a contribution value of competence to the performance of administrative staff of 17.9% while the remaining 82.1% is influencing by other factors besides competence.